Maillard reaction affecting immunobinding activity and digestibility of tropomyosin in Alectryonella plicatula food matrix - Chenchen Yu; Xinrong He; Nairu Ji; Shuai Kang; Dongxiao Li; Huilin Zhang; Yang Yang; Dong Lai; Qingmei Liu; Guangming Liu (Food Science and Human Wellness)
In recent years, the allergy rate of oysters has surged, and daily food processing methods make it hard to reduce heat resistance and digestive allergy such as tropomyosin (TM). In this study, the Maillard reaction with xylose significantly reduced the IgE binding capacity of Alectryonella plicatula food matrix (AFM), that reduced by (77.81 ± 2.68)%. The study found the Maillard reaction changes the structure of the AFM, in which the content of α-helix decreased by (24.64 ± 1.46)%. Structural transformation further explains why the Maillard reaction alters the immunobinding activity of AFM. In addition, the Maillard reaction reduces the digestive stability of the AFM and makes TM in the A. plicatula food matrix Maillard reaction products (AFM-MRPs) more easily digested. Based on the above research, 10 amino acids on the 7 IgE epitopes of TM were modified. This result indicates that the Maillard reaction reduces the immunobinding activity of the AFM by changing the structure and modifying the amino acids on the epitope.